ASPEK HUKUM KEGIATAN BISNIS DAN FUNGSI PERIZINAN DI INDONESIA DALAM KERANGKA MASYARAKAT EKONOMI ASEAN 2015 - Haykal, Hassanain (Veritas et Justitia, 2016)
The ASEAN Economic Community (MEA) should be perceived as a joint commitment to establish a (regional) single market within which there would be a free flow of goods and services. This commitment at the regional level inadvertently forces member countries to adjust their national laws and regulations. To be more concrete, simplifying the permit system and bureaucratic streamlining becomes a must.  On the other hand, the huge flow of incoming and outgoing trade and services, put pressure to national government to establish a viable control and monitoring system.  Reformation of the existing licensing system should be done by identifying overlapping rules and modernizing the government bureaucracy.  Keywords: permits/licensing, Economic ASEAN Community, bureaucratic reform